Play therapy - "Axline, Virginia M." (New York, 1947)
Play therapy gives a child a vital opportunity to "play out" his feelings and problem- his fears, hatred, loneliness, and feelings of failure and inadequacy. Here is an intensity practical book that gives specific illustrations of how therapy can be implemented in play contacts, and tells how the toys of the playroom can be vivid performers and aids in growth.
Keywords: Child psychology